Strain and threshold reduction for a multi-wavelength blue–green laser-triad. (25th June 2019) - Sadasivan, Viswas; Paliwal, Avinash; Mathew, Manish
Abstract: Ocean water has a varying transmission around a blue–green window with maximum shifting from blue to green based on chlorophyll and other contained impurities. Here, heterostructure strain accommodation methods necessary to make a three-wavelength InGaN-AlGaN-GaN laser-triad have been studied using simulations. The effect of the GaN/AlGaN doped superlattice (SL) on strain accommodation at the GaN-AlGaN interface has been studied, and Al% twice the bulk layer has been found to be sufficient. InGaN/GaN SL has also been studied to reduce the strain in the InGaN/GaN multi-quantum well active layer and thereby allowing greater In%. Further, a 7 times reduction in the green laser threshold has been obtained by using a superlattice barrier for the quantum well (QW), which also creates asymmetry in the QW. The laser triad is potentially useful in making underwater communication links that can adapt to the optical transmission of the water.